Association of Systemic Lupus Erythematosus With Uranium Exposure in a Community Living Near a Uranium‐Processing Plant: A Nested Case–Control Study. Issue 11 (November 2014) - Lu‐Fritts, Pai‐Yue; Kottyan, Leah C.; James, Judith A.; Xie, Changchung; Buckholz, Jeanette M.; Pinney, Susan M.; Harley, John B.
<x xml:space="preserve">Abstract</x> Objective To explore the hypothesis that cases of systemic lupus erythematosus (SLE) would be found more frequently in community members with high prior uranium exposure in the Fernald Community Cohort (FCC). Methods A nested case–control study was performed using data from the FCC, a volunteer population of individuals who had resided near a uranium ore–processing plant in Fernald, Ohio during the years of plant operation; uranium plant workers were excluded. Members of the FCC were monitored for 18 years. SLE cases were identified using the American College of Rheumatology 1997 revised classification criteria, laboratory testing, and medical record review. Each case was matched to 4 controls by age, race, and sex. Sera from potential cases and controls were screened for autoantibodies. Cumulative exposure to uranium particulates was calculated using a dosimetry model. Logistic regression with covariates was used to calculate the odds ratios (ORs) with 95% confidence intervals (95% CIs) for the probability of an association between uranium exposure and SLE. Results The FCC comprised 4, 187 individuals with minimal levels of uranium exposure, 1, 273 with moderate exposure, and 2, 756 with high exposure. The diagnosis of SLE was confirmed in 23 of 31 individuals who had been assigned International Classification of Diseases, Ninth Revision codes for lupus, and was also confirmed in 2 of 43 individuals who had been prescribed hydroxychloroquine. The female to male ratio was 5.25:1. Of the 25 confirmed SLE cases, 12 were in the high exposure group. The presence of SLE was associated with higher levels of uranium exposure (OR 3.92, 95% CI 1.13–13.59; P = 0.031). Conclusion High uranium exposure is associated with SLE, as compared to matched controls, in this sample of uranium‐exposed individuals. Potential explanations for this relationship include possible autoimmune or estrogen effects of uranium, somatic mutation, epigenetic effects, or effects of some other unidentified accompanying exposure.